2010
DOI: 10.1016/j.aquatox.2010.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic exposure to tetrabromobisphenol A and its metabolites, bisphenol A and tetrabromobisphenol A dimethyl ether disrupts normal zebrafish (Danio rerio) development and matrix metalloproteinase expression

Abstract: Tetrabromobisphenol A (TBBPA) is a widely used brominated flame retardant that is persistent in the environment and detected in human serum and breast milk. TBBPA is microbiologically transformed in anaerobic environments to bisphenol A (BPA) and in aerobic environments to TBBPA dimethyl ether (TBBPA DME). Despite the detection of TBBPA DME in the environment, the resulting toxicity is not known. The relative toxicity of TBBPA, BPA and TBBPA DME was determined using embryonic exposure of zebrafish, with BPA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 53 publications
5
42
2
Order By: Relevance
“…Here we showed that TCBPA is a more potent chemical than either TBBPA or BPAF. Our results of post-hatch survival in exposed embryos/larvae are in accord with the findings from previous work examining post-hatch survival of embryos at 3 lM (1.6 mg/L) of TBBPA with 100% mortality (McCormick et al, 2010). We found that H-BPAs exposure results in a variety of developmental lesions in the embryos/larvae, such as a delay in time to hatch, and vascular lesions (edema and hemorrhage).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Here we showed that TCBPA is a more potent chemical than either TBBPA or BPAF. Our results of post-hatch survival in exposed embryos/larvae are in accord with the findings from previous work examining post-hatch survival of embryos at 3 lM (1.6 mg/L) of TBBPA with 100% mortality (McCormick et al, 2010). We found that H-BPAs exposure results in a variety of developmental lesions in the embryos/larvae, such as a delay in time to hatch, and vascular lesions (edema and hemorrhage).…”
Section: Discussionsupporting
confidence: 82%
“…We found that H-BPAs exposure results in a variety of developmental lesions in the embryos/larvae, such as a delay in time to hatch, and vascular lesions (edema and hemorrhage). Although recent work reported that embryos exposed to BPA and TBBPA would lead to tail malformation (Duan et al, 2008;McCormick et al, 2010), it was not observed in all embryos/larvae in this study.…”
Section: Discussioncontrasting
confidence: 50%
“…TBBPA is very persistent and has been detected in a wide range of environmental media, including air, water, soil and sediment (de Wit et al, 2010;Song et al, 2014;Xiong et al, 2014), and even in human tissues and plasma (Fujii et al, 2014a, b). TBBPA persists due to its high lipophilicity (log K ow ¼ 5.9), low volatility (7.0 Â 10 À11 atm m 3 mol À1 ), low water solubility (4.16 mg L À1 at 25 C in H 2 O) and recalcitrance (McCormick et al, 2010). Unfortunately, the evidence increasingly highlights the possible toxic effects of TBBPA (Decherf et al, 2010;An et al, 2011;Koike et al, 2013;Linhartova et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that BPA may be eventually formed in the NS-nZVI system if the reaction lasted for longer time periods as indicated in Lin et al (2012), but its concentration would be much lower than in the S-nZVI system. Nevertheless, rapid formation of BPA in the S-nZVI system should be considered as an advantage over the NS-nZVI system since BPA is less toxic and readily degradable than brominated BPA (McCormick et al, 2010;Chang et al, 2012;Yang and Chan, 2015). On the basis of the transformation products identified in this study, the transformation pathways of TBBPA in the S-nZVI and NS-nZVI systems were proposed (Text S3 and Fig.…”
Section: Products and Pathways Of Tbbpa Transformation By S-nzvi Andmentioning
confidence: 99%